2014
DOI: 10.1128/jcm.00398-14
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-Outbreak of Pre-Extensively Drug-Resistant (Pre-XDR) Tuberculosis in Kinshasa: Collateral Damage Caused by False Detection of Fluoroquinolone Resistance by GenoType MTBDR sl

Abstract: f Fluoroquinolones are the core drugs for the management of multidrug-resistant tuberculosis (MDR-TB). Molecular drug susceptibility testing methods provide considerable advantages for scaling up programmatic management and surveillance of drugresistant TB. We describe here the misidentification of fluoroquinolone resistance by the GenoType MTBDRsl (MTBDRsl) (Hain Lifescience GmbH, Nehren, Germany) line probe assay (LPA) encountered during a feasibility and validation study for the introduction of this rapid d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
1
14
2
1
Order By: Relevance
“…Six percent of FQ resistance, as classified by MTBDRsl, was due to the sole absence of WT probe hybridization. Our results contrast significantly with the results of two studies conducted in the Congo and the Democratic Republic of Congo, where over 60% of FQ resistance was attributable to the sole absence of WT probe hybridization (17,18). Our results more closely resemble those reported by Brossier et al (33) and Huang et al (34), in which less than 20% of FQ resistance was attributable to the sole absence of WT probe hybridization.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…Six percent of FQ resistance, as classified by MTBDRsl, was due to the sole absence of WT probe hybridization. Our results contrast significantly with the results of two studies conducted in the Congo and the Democratic Republic of Congo, where over 60% of FQ resistance was attributable to the sole absence of WT probe hybridization (17,18). Our results more closely resemble those reported by Brossier et al (33) and Huang et al (34), in which less than 20% of FQ resistance was attributable to the sole absence of WT probe hybridization.…”
Section: Discussioncontrasting
confidence: 57%
“…Although MTBDRsl detects resistance to FQ, SLID, and ethambutol, phenotypic resistance to ethambutol was not performed as part of this study, and consequently only resistance to FQ and SLID were assessed. MTBDRsl probes detect mutations in codons 85 to 97 of the gyrA gene positions 1401 to 1402 and position 1484 of the rrs gene (17,23). Mutations associated with FQ resistance are detected by mutation probes gyrAMUT1(A90V), gyrAMUT2(S91P), gyrAMUT3A(D94A), gyrAMUT3B(D94N/Y), gyrAMUT3C(D94G), and gyrAMUT3D(D94H); mutations associated with resistance to SLID are detected by mutation probes rrsMUT1(A1401G) and rrsMUT2(G1484T).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…tuberculosis lineage 4), we speculated that the gyrA double mutant strains might constitute a subgroup of the Uganda genotype (16, 17). This hypothesis appeared to be consistent with the results of two studies from the Republic of the Congo and the Democratic Republic of the Congo, which reported the highest frequency of these double mutants (in 60% [9/15] versus 7.2% [15/209] of MDR TB cases from Brazzaville and Pointe-Noire versus Kinshasa, respectively) (7, 8). This was further supported by mycobacterial interspersed repetitive-unit–variable-number tandem-repeat (MIRU-VNTR) results (7, 15).…”
Section: Textsupporting
confidence: 89%